Renal imaging: a comparison of radionuclide, ultrasound, and computed tomographic scanning in investigation of renal space-occupying lesions. - O'Reilly, P H (1981)
Two studies were carried out in which 27 and 23 patients respectively with renal space-occupying lesions were assessed by different techniques and the results compared. Instead of proceeding to renal arteriography after the lesion had been found on urography, radionuclide and ultrasound scanning were used in the first study to clarify the nature of the lesions, while in the second study computed tomography was used as well. Results were good with all three methods, although ultrasonography and radionuclide scanning cannot resolve lesions of under 2 cm in diameter and the radiation dose with computed tomography is similar to that used in renal arteriography. Probably the best method of evaluating renal space-occupying lesions after urography is to use both ultrasound and radionuclide scanning. If further information is required computed tomography or arteriography is indicated.